Exploring phenomenology for researching lived experience in Technology Enhanced Learning - Oberg, Hans; Bell, Alex (Proceedings of the International Conference on Networked Learning, 2012)
This paper explores the roots and presents some forms of phenomenology starting with the origin of Husserl's phenomenology and his notion of going back to things as they are in order to seek their essences. The paper then looks at the different perspectives, starting with the empirical phenomenology: its disciplinary linkage to psychology, its focus on the phenomenon itself, and the analysis of the structural in order to discern how structures speak. Existential phenomenology, on the other hand, sees human experiences of the world as being worth studying, where we are not only epistemological spectators in the world but are also ontologically embedded in it. Finally, Hermeneutic phenomenology acknowledges that humans have prejudices and their preconceptions from their experiences are nearly impossible to ignore. Understanding is achieved through dialogue. The hermeneutic circle refers to the interplays between our self-understanding and our understanding of the world, and entails an existential task with which each of us is confronted. The paper then focuses on the authors' experiences during our PhD research. The paper highlights some differences in research approaches, aligned to different subtle perspectives, which offers the researcher flexibility. The aim for this paper has been to engage the networked learning community in discussing the suitability of choosing phenomenology as a research methodology. A snapshot in the exploration of the researchers decisions to use phenomenology for Technology Enhanced/Networked Learning research is presented and their reflections on their progress to discern the differences between the choices we made in developing our respective research designs. Some of the reasons behind our decisions, with the purpose of entering into dialogue with the Technology Enhanced/Networked Learning community, are presented.